2015
DOI: 10.1080/13674676.2015.1011370
|View full text |Cite
|
Sign up to set email alerts
|

The churches and well-being: perspectives from the Australian National Church Life Survey

Abstract: Australia is a nation with high levels of recorded well-being. This paper introduces a collection of papers which are concerned with the intersections between well-being and religion in an Australian context. The research is conducted on a religious population, namely Christian church attenders and local church leaders (both clergy and lay) in congregations in the Australian National Church Life Surveys (NCLS), perhaps the largest database on church life in the world. The NCLS covers more than 20 Protestant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Congregations where "… higher percentages of attenders always feel inspired are also more likely to be growing churches." (Powell et al, 2012). In comparing the responses of the attenders who always or usually find the worship inspiring (see Figure 1) it can be seen that there was an improvement from 2010 to 2014.…”
Section: Vital and Nurturing Worship As A Core Qualitymentioning
confidence: 91%
See 1 more Smart Citation
“…Congregations where "… higher percentages of attenders always feel inspired are also more likely to be growing churches." (Powell et al, 2012). In comparing the responses of the attenders who always or usually find the worship inspiring (see Figure 1) it can be seen that there was an improvement from 2010 to 2014.…”
Section: Vital and Nurturing Worship As A Core Qualitymentioning
confidence: 91%
“…The core elements are an important part of the congregational voice as the different elements have a cumulative effect, "… on its own has only a small impact, but together their effect is substantial" (Powell et al 2012).…”
Section: Vital and Nurturing Worship As A Core Qualitymentioning
confidence: 99%
“…The Australian National Church Life Survey is now a well-established instrument for assessing congregational opinions and attitudes across a wide range of Christian denominations (see http://www.ncls.org.au/default.aspx?sitemapid=7086). Surveys were conducted in 1991, 1996, 2001, 2006, and 2011, and the findings have been widely disseminated (Bellamy et al, 2006; Kaldor, Bellamy, Correy, & Powell, 1992; Kaldor et al, 1995; Kaldor, Bellamy, Powell, Hughes, & Castle, 1997; Kaldor, Bellamy, Powell, Castle, & Hughes, 1999; Kaldor, Dixon, et al, 1999; Kaldor & McLean, 2009; Pepper, Sterland, & Powell, 2015; Powell et al, 2012; Powell & Robbins, 2015).…”
Section: Psychological Type Theorymentioning
confidence: 99%
“…Additionally, age, sex, education level and denominational groups will be employed as further control variables. (Kaldor, Bellamy, Correy, & Powell, 1992;Kaldor, Bellamy, Moore, Powell, Castle, & Correy, 1995;Kaldor, Bellamy, Powell, Hughes, & Castle, 1997;Kaldor, Bellamy, Powell, Castle, & Hughes, 1999;Kaldor, Dixon, Powell, Bellamy, Hughes, Moore, & Dalziel, 1999;Bellamy, Cussen, Sterland, Castle, Powell, & Kaldor, 2006;Kaldor & McLean, 2009;Powell, Bellamy, Sterland, Jacka, Pepper, & Brady, 2012;Pepper, Sterland, & Powell, 2015;Powell & Robbins, 2015).…”
Section: Research Questionmentioning
confidence: 99%
“…Prior to COVID-19, Dunne et al (1997) found in a sample of 1631 adult Australian churchgoing Catholics that frequent church attendance was related to lower neuroticism and psychoticism scores with a modest effect size. The National Church Life Survey's 2011 data set generated several studies of adult churchgoing Christians and psychological wellbeing in Australia, including some Catholic data, but found few differences between Catholics and Protestants (Francis et al, 2016;Powell & Pepper, 2015;Powell & Robbins, 2015).…”
Section: Introductionmentioning
confidence: 99%